Weaver’s Music: Folk Songs and Creative Industries in Bangladesh - Rabbani, Golam (Advances in Social Sciences Research Journal, 2026)
Traditional folk industries in Bangladesh, from handloom weaving and embroidery to pottery, metal crafts, and vernacular arts, contribute to cultural heritage and to a broad understanding of the creative economy. This article examines how these folk industries support creative economic development and national identity in Bangladesh. Drawing on creative-industry approaches, including Hesmondhalgh’s cultural industries, Florida’s creative class, and Caves’s economic properties, I analyze twelve craft-associated folk songs presented only in English translation. The songs are treated as social texts that encode themes of cultural labour, place-based identity, intangible heritage, gendered economies, and the transformation of cottage industries within commercial value chains. Using qualitative textual analysis, I interpret each song’s symbolism in dialogue with creative-economy scholarship. The analysis reveals a layered narrative: artisans demonstrate strong intrinsic commitment to craft and place-rooted creativity, yet face structural problems such as intermediary extraction, marginalization within policy, and the disruptive effects of mechanization. The discussion argues that centering grassroots cultural workers expands the creative economy concept beyond Western, urban frameworks and strengthens development debates by foregrounding equity and cultural rights.